(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2012)
Influence of components of potassium persulfate (PP)–dimethylamino-ethanol (DMAE) initiating system on sodium pentadecylsulfonate (PDSN) micelle formation has been studied using various physico-chemical methods. It has been shown that under the influence of compounds the critical concentration of micelle formation decreases. Intermolecular interactions in PDSN–H2O–DMAE (PP) system has been discussed on the base of density changes.